Evaluasi Pelayanan Informasi Obat Berbasis Syariah terhadap Tingkat Kepuasan Pasien di Apotek Aletheia Semarang - Rini, Tri Diana Puspita; Evali, Walensa; Pebriana, Winda (Sultan Agung Islamic University of Semarang, 2025)
Background: Pharmacy is a health service facility that is very easy to reach by the public. Drug information services for patient satisfaction are very important in ensuring the quality of health services received by patients. This sharia-based approach not only meets pharmaceutical service standards but also adds emotional and spiritual value to patients, making it a relevant innovation in pharmaceutical services in Indonesia. This study aims to evaluate sharia-based drug information services at Aletheia Pharmacy and its impact on patient satisfaction levels. Method: This study uses a cross-sectional design method, to collect data from patients who receive drug information services at pharmacies. This research method includes direct observation of the drug information service process, and the dissemination of questionnaires to patients. The validity test results produced an r value for each statement > 0.361 (Valid). The reliability test was carried out using the Cronbach Alpha >0.6 (Reliable) test for each questionnaire item. Results: The Result of the research on the level of patient satisfaction according to the test using a questionnaire were found that the average patient was satisfied as much as 57.95%, very satisfied 37.74% and hesitant as much as 4.31%. Conclusion: it shows that sharia-based Drug Information Services have a significant influence on the level of patient satisfaction in Aletheia Pharmacy.